PATIENTS’ OUTCOME AND COMPLIANCE IN OBESITY CLINIC HOSPITAL KAJANG – A RETROSPECTIVE AUDIT OF WEIGHT LOSS INTERVENTIONS - Marimuthu, Varuna Shashti Dhevi; Katiman, Elliyyin; Aziz, Hazwani (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION The primary goals of this audit were to assess outcome and compliance with the Obesity Clinic program Hospital Kajang. The outcomes were measured by weight change, blood pressure, low density lipoprotein (LDL), and glycaemic control. Compliance was assessed by the number of defaulters and adherence to prescribed dietary recommendations. METHODOLOGY The audit was conducted by the Endocrine Team of Hospital Kajang starting from January till December 2024. A total of 37 patients who attended two or more sessions were included. Data was collected from patient records, including anthropometric, laboratory investigations and treatment adherence. RESULT The average baseline BMI of patients is 44.47 kg/m² and 37% of patients have diabetes. A total of 75.7% of patients achieved at least 5% weight loss throughout the follow-up. Mean weight reduction was 2.997 kg (p = 0.012). Systolic blood pressure (p = 0.385) and LDL (p = 0.894) did not show significant changes throughout follow-up. HbA1c among diabetes patients also showed no significant changes (p = 0.243). Adherence to treatment was reported in 75.7%, while 97.3% of patients returned for follow-up. CONCLUSION This audit demonstrates that the Obesity Clinic at Hospital Kajang is effective in facilitating weight reduction. While most patients achieved weight loss, clinical improvements in metabolic parameters were not statistically significant. Future interventions should focus on improving adherence to reinforce long-term outcomes.